Surgical Correction Of Atresia Ani In A Lamb - Arora, Neeraj; Chaudhary, R.N.; Potliya, Sandeep; Dinesh ,; Pal , Madan (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Atresia ani is a congenital defect and may be caused by genetic disorders (chromosomes or transgenes), environmental factors (management technique, infections, toxins or fertilization methods) or combination of both (Cassini et al., 2005). Monsang et al. (2011) reported a case of double vulva with atresia ani in a cross bred calf. The present report records a case of atresia ani in a lamb and corrected surgically.